Dalekopisowy morski list przewozowy a konosament - Hołowiński, Jan (Wydział Prawa i Administracji UAM, 1974)
The Atlantic Container Line, being a maritime carrier of goods, introduced a new transportation document, which needs some explanations and a juridical analysis. The new document consists of two seperate documents: in the port of loading the shipper of the goods receives a freight receipt, in which all particulars concerning the goods and its transport are duly given. The shipper has a choice: instead of such a freight receipt he may ask for a normal bill of lading. But the conditions of carriage are the same both according to the freight receipt as well as according to the bill of lading. There is only one major difference: the bill of lading may be delivered to the order of the shipper or to the bill of lading holder, whereas the freight receipt must bear the exact name of the consignee. In consequence the freight receipt is not a document which entitles its holder to dispose of the cargo. The freight receipt is delivered to the shipper and remains in his hands. The freight receipt is being drawn up by the carrier or his agent in the port of loading on a telex apparatus, which has a connection with the carrier's agent apparatus at the port of discharge. There, at the same time, a „notice of arrival" is being written by the telex receiver apparatus. This notice of arrival (of the cargo) is being delivered to the consignee, who with that document in hand may take delivery of the cargo. The whole terminology is a new one. Maritime law does not know a freight receipt (it knows merely a mate's receipt which has other functions) nor a notice of arrival of the cargo in form of a document of title. And therefore the legal status of these two documents, considered together as one document of transport, must be found. According to Polish civil law the two mentioned documents together may be identified with a freight bill, a document which is being met with in other branches of the transportation industry. The prefix „telex" should denote that the document is not transferred in its material form (as a piece of paper) but on„wires" with the aid of electronic apparatus. At the port of discharge the document is being drawn up once more. This facilitates enormously maritime trade if and when a bill of lading is not needed. And a bill of lading is not needed when the partners of the selling contract are in constant contact and have a full confidence that the contract will be fulfilled in the agreed manner and time. Such a situation may be found in relations between enterprises of socialist countries. Therefore the maritime telex freight bills could be successfully used in these countries.
Telex Maritime Freight Bill and Bill of Lading